MAKNA LAKI-LAKI PEMANGGUL GONI DALAM CERITA PENDEK “LAKI-LAKI PEMANGGUL GONI” KARYA BUDI DARMA - Titik Wijanarti (Balai Bahasa Sulawesi Tengah, 2016)
Literary works written by Budi Darma has its own peculiarities or characteristics when compared with theother literary works. This study examines a short story by Budi Darma entitled “Laki-Laki Pemanggul Goni”.The problem in this research is the meaning behind of laki-laki pemanggul goni in the short story. The purposeof research is to describe the meaning of laki-laki pemanggul goni in the short story “Laki-Laki PemanggulGoni”. The method in this study is descriptive analysis with semiotic theory. Based on semiotic analysis, themeaning of laki-laki pemanggul goni in the short story is representation of Karmain’s guilt that he had done in the past.